Gold-catalyzed intramolecular animation of alcohol pro-electrophiles as novel synthetic strategies to nitrogen heterocycles - Prasath Kothandaraman (2011)
The work of this thesis has been directed towards establishing gold-catalyzed intramolecular amination of alcohol pro-electrophiles as novel synthetic strategies to nitrogen heterocycles. This thesis is divided into three parts: